Effect of ipil ipil and bean leaves supplementation on egg production, egg quality and growth performance of Japanese quail (Coturnix japonica) - Sarkar, Sumon; Aziz, Fahima Binthe; Hasan, Md Mahmudul; Islam, Rakibul; Parvez, Misrat Masuma (Asian Journal of Medical and Biological Research, 2018)
This study was conducted to determine the effect of ipil ipil and bean leaves supplementation on egg production, egg quality and growth performance of Japanese quail. A total of 40 “Japanese Quail” at the age of 42 days (06 weeks) old were divided into four groups T0, T1, T2 and T3 respectively. Group T0 was considered as control which fed only with commercial layer ration. Group T1 was supplemented with formulation of 2 gm grinded ipil ipil leaves, Group T2 with 2 gm grinded Bean leaves and Group T3 with 2 gm grinded ipil ipil leaves plus 2 gm grinded Bean leaves per kg feed respectively. Observations were recorded for growth performance, egg production and egg quality of quail. Increased egg production rate was observed in ipil ipil supplemented groups (group T1). Body weights were increased significantly (p<0.05) in all treated groups in respect to the control and highest was recorded in combined ipil ipil and Bean leaves supplemented groups (Group T3). In treatment groups, there were significant increase in egg production, but in case of control group, the egg production was not increased. There was no significant pathological change in any internal organs of the layer of treated groups. Best result was found in the group T3. The present study reveals that combined supplementation of ipil ipil and bean leaves gives better result over the other groups in respect to growth performance, egg production and egg quality. Asian J. Med. Biol. Res. June 2018, 4(2): 201-206